Design of Compact MIMO Multiband Antenna for Wireless Radio Communication Application - Anand, C. (IRO Journal on Sustainable Wireless Systems, 2021)
Slot and patch modification for the design of a compact multiband antenna with Multi-Input-Multi-Output (MIMO) functionality is proposed in this paper. At various frequency bands, the antenna performance is obtained by modification and addition of slot and patch shapes in the design of the compact MIMO multiband antenna. Addition of slots or patches is done separately in the already existing multiband antenna designs. Whereas in this work, the addition of slot and patch are combined. Arlon Diclad 880 with a dielectric constant of 2.17 - 2.2 (εr) and height 0.75mm is used for the antenna design. The MIMO multiband antenna with the dimension of 12.5 mm × 7.5 mm is designed. On various millimeter-wave frequency bands ranging from 20 GHz to 40 GHz, the MIMO antenna can function as observed in the results of simulation and evaluation. This work shows that microstrip antennas can be added with slots and patches during their design and development, thereby enabling the antenna to operate under multiple frequency bands.